Non-muslims, Islam and muslims in Malaysia - Moten, Abdul Rashid; Wok, Saodah; Ushama, Thameem (Asian Research Service, 2009)
Malaysia is generally accepted by political scientists and sociologists as a 'divided society'. This concept posits profound and persistent cleavages within Malaysian society among various ethnic groups. However, contrary to expectations, Malaysia is widely accepted as a country where the different ethnic groups have co-existed peacefully and maintained racial harmony in a post-colonial context. The Malaysian political system is based upon a 'power sharing' formula whereby the ethnic communities form a grand coalition to rule and respect each other's way of life. Theories of interethnic relations usually focus on how state authority enables credible commitments to interethnic political bargains ensuring interethnic cooperation. However, peaceful coexistence also depends upon the opinions held by ethnic groups about each other's religion and behavior. This study, based upon survey data, analyses the opinions of non-Muslims about Islam and Muslims in Malaysia. The discussion is preceded by an overview of historical forces and factors that made Malaysia a plural society with people of many faiths and races living in harmony.